Garantias ao cumprimento da obrigação tributária: depósito; fidejussória; penhora; cautelar (com ou sem intervenção judicial); e outras - Castro, Danilo Monteiro de (2020)
The present study aims to analyze the guarantees for the fulfillment of the tax obligation from a different perspective, that is, for the effects they generate, some of them peculiar to this field of law: suspension of the enforceability (article 151, subsection II, of the National Tax Code); and cessation of indirect charges (article 206 from the same Code). The perspective in question provides a different systematization of that subject, what motivated us to segregate it from such effects and, with that, to indicate existing pragmatic mistakes that generates legal insecurity, for allowing casuistic decisions, not supported by precise definitions, whether it is a guarantee of mandatory compliance or, mainly, the specific effects arising from it when performed in a tax environment. We then sought to clarify these points in order to sequentially evince the problems generated by the superficiality with which they are treated and, then, to suggest solutions that are more harmonious and consistent with the rules in force. Thus, upon a hermeneutic-analytic investigation, the legal system of positive right in law will be analyzed and, therefore, interpreted, so that reflections on the theme are possible, and a language with scientific claims